Actinide Endohedral and Exohedral Cubic Siloxanes: An(IV)@(HSiO1.5)8 and An(IV)&(RSiO1.5)8 (An = U, Np, Pu; R = H, Cl, OH). Issue 43 (12th November 2019) - Duan, Meigang; Li, Peng; Zhao, Huifeng; Wu, Jizhou; Li, Yuqing; Liu, Wenliang; Fu, Yongming; Xie, Feng; Ma, Jie
Abstract : Actinide metallasilsesquioxanes and their distinctive bonding properties have received an increased attention due to their potential value in advanced nuclear science and biomedicine. Herein, we have proposed a new class of endohedral An(IV)@(HSiO1.5 )8 and exohedral An(IV)&(RSiO1.5 )8 (An = U, Np, Pu; R = H, Cl, OH) metallasilsesquioxanes combing an actinide atom with cubic siloxanes (T8 cage) and used density functional theory calculations to investigate the electronic structures of actinide metallasilsesquioxanes. The larger binding energies and the higher minimum vibration frequency indicate An(IV)@(HSiO1.5 )8 and An(IV)&(HSiO1.5 )8 clusters are considerable stability. The strong interactions of An–O bonds are checked by the large Fuzzy bond orders and the obvious charge transferring from O of T8 cage to An. Furthermore, the quantum theory of atom in molecules and electron localization function are implemented to analyze the chemical bonding characterizations, which implies electrostatic and covalent interaction play comparable important roles in the An–O bonds. The covalent interaction is more obvious in An(IV)&(HSiO1.5 )8 clusters than that in An(IV)@(HSiO1.5 )8 clusters. Our results show that the energy of An(IV)@(HSiO1.5 )8 clusters are lower than that of An(IV)&(HSiO1.5 )8 clusters. We theoretically simulated infrared and ultraviolet‐visible (UV/Vis) spectra feature for An(IV)@(HSiO1.5 )8 clusters. These spectral characteristics can be used to identify the cluster of An(IV)@(HSiO1.5 )8 in the future experimental investigations. Besides, our calculation reveals that (OHSiO1.5 )8 has better adsorption capacity than (HSiO1.5 )8 and (ClSiO1.5 )8 for actinides cations. Thus, this work not only describes a new method for encapsulating radioactive actinides, but also provides a new material for removing actinides. Abstract : In this study, a new class of endohedral An(IV)@(HSiO1.5 )8 and exohedral An(IV)&(RSiO1.5 )8 (An = U, Np, Pu; R = H, Cl, OH) metallasilsesquioxanes combing an actinide atom with cubic siloxanes (T8 cage) have been proposed. The electronic structures, bonding characterization, orbital interactions, topological properties and spectra feature of actinide endohedral (An(IV)@(HSiO1.5 )8 ) and exohedral (An(IV)&(RSiO1.5 )8 ) cubic siloxanes were systematic investigated, which provided a valuable reference for disposal of radioactive actinides.